A humanized anti-CD26 monoclonal antibody inhibits cell growth of malignant mesothelioma via retarded G2/M cell cycle transition. Issue 1 (December 2016) - Hayashi, Mutsumi; Madokoro, Hiroko; Yamada, Koji; Nishida, Hiroko; Morimoto, Chikao; Sakamoto, Michiie; Yamada, Taketo
Abstract Background Malignant Mesothelioma (MM) is a highly aggressive tumor with poor prognosis. Multimodal treatments and novel molecular targeted therapies against MM are in high demand in order treat this disease effectively. We have developed a humanized monoclonal antibody YS110 against CD26 expressed in 85 % of MM cases. CD26 is thought to be involved in tumor growth and invasion by interacting with collagen and fibronectin, or affecting signal transduction processes. Methods We evaluated the direct anti-tumor effect of YS110 against MM cell lines, NCI-H2452 and JMN, and investigated its effects on cell cycle and on the cell cycle regulator molecules. In addition, we investigated synergistic effects of YS110 and anti-tumor agent pemetrexed (PMX) against MM cell line both in vitro and in vivo. Results YS110 suppressed the proliferation of NCI-H2452 cells by approximately 20 % in 48 h. Based on cell cycle analysis, percentage of cells in G2/M phase increased 8.0 % on the average after YS110 treatment; in addition, cell cycle regulator p21 cip/waf1 was increased and cyclin B1 was decreased after YS110 treatment. Inhibitory phosphorylation of both cdc2 (Tyr15) and cdc25C (Ser216) were elevated. Furthermore, activating phosphorylation of p38 MAPK (Thr180/Tyr182) and ERK1/2 (Thr202/Tyr204) were augmented at 24 h after YS110 treatment. PMX rapidly induced CD26 expression on cell surface and the treatment with both YS110 and PMX inhibited in vivo tumor growth accompanied by a synergistic reduction in the MIB-1 index. Conclusion This is a first report of a novel anti-proliferative mechanism of the humanized anti-CD26 monoclonal antibody YS110, which resulted in G2/M cell cycle delay through regulation of quantity and activity of various cell cycle regulating molecules.